A study on the effectiveness of the role of board of visiting justices and board of visitors under the prison act 1995 and child act 2001 / Salmah Roslim ...[et al.] - Roslim, Salmah; Manshor, Nurul Mazrah; Hussin, Rohayati; Mohamad Sirat, Nur Irinah (Institute of Research Management & Innovation (IRMI), 2015)
In Malaysia, the Board of Visiting Justices and Board of Visitors are governed under the different legislations. Board of Visiting Justices is governed under Prison Act 1995 and Board of Visitors is governed under Child Act 2001. Generally, both Board of Visiting Justices and Board of Visitors are under duties to protect the interest, welfare and supervise the development level of child and young offender. Meanwhile, the Prison Act 1995 provides the overall duties of Board of Visiting Justices such as visiting any prison in the state for which he is appointed, inspecting the wards, cells and other divisions of the prison, inspecting the quality and quantity of prisoners’ food, hearing any complaints from prisoners and questioning any prisoner or prison officer to ascertain whether provisions of the law are adhered to. Accordingly, this research seeks to tackle several issues regarding the effectiveness of Board of Visiting Justices and Board of Visitors under the Prison Act 1995 and Child Act 2001 in carrying out their duties. Methodologically, it will employ a qualitative approach involving semi-structured interviews with various stakeholders including government and enforcement agencies under the relevant ministries. The outcomes of the semi-structured interview with the relevant respondents will be analyzed to ensure whether the roles of the Board of Visiting Justices and Board of Visitors have been discharged accordingly. Therefore, this research will aid the conceptualization towards the efficiency of Board of Visiting Justices and Board of Visitors under the Prison Act 1995 and Child Act 2001. The findings would be greatly benefited the policy makers, the judiciary, the enforcement agencies and public at large.